Implementasi Manajemen Kurikulum di SMA Negeri 1 Cerme: Indonesia - Nissa, Alfiani; Setyowati , Sulis; Azzahra, Aghis Waldata; Yasmitha, Ifania; Ayu Wulandari (CV Putra Publisher, 2024)
This study aims at curriculum management at SMA Negeri 1 Cerme, focusing on planning, implementation, and evaluation. Using a qualitative descriptive method, data were collected through in-depth interviews with the Vice Principal for Curriculum, observation of management practices, analysis of supporting documents. The results showed that the curriculum planning stage was carried out systematically by considering educational objectives, mapping basic competencies, and providing adequate teaching materials. The implementation stage includes learning time allocation policies, conversion of practice hours, determination of minimum hours of subjects, and preparation of a structured academic calendar. However, the evaluation stage of curriculum management is still incidental, carried out only when certain obstacles arise, without a systematic and sustainable approach. This study recommends the need to strengthen the capacity of educators through continuous training and the application of technology to support the monitoring and evaluation process. In addition, intensive collaboration between schools, educators, students and communities is needed to ensure the active involvement of all stakeholders in the curriculum management process.